(untitled) (Global Journals of Research in Engineering, 2011)
Microgrids (MG) are new concept of electric power networks consisting of distributed generation (DG), , renewable energy resources and sensitive loads. The goal of microgrid operation is to provide reliable and high-quality electric power regardless of faults or abnormal operating conditions. Many control methods have been employed to regulate the output power of DGs used in MGs. This paper presents a control scheme for DGs of a power system, especially with voltage source inverter (VSI) interface, for both grid connected and islanded modes. A comprehensive study has been performed through PSCAD simulations of the inverter- fed MG behavior under both islanding and connected operation for different load conditions. The simulation results prove the droop method efficiency in controlling the voltage and frequency of the inverter output which is connected to the loads.